Forage intake and feeding behaviour of day and/or night grazing cattle in sahelian rangelands - Ayantunde, Augustine A.; Fernández Rivera, A.; Hiernaux, Pierre H.Y.; Keulen, H. van; Udo, H.M.J. (CAB International, 1999)
Forage intake and feeding behaviour of cattle grazing during day and/or night was studied in Sadore between February and May (late dry season) 1995 and, in Toukounous, Niger, between July 1995 and May 1996, covering wet (WS), early dry (EDS) and late dry (LDS) seasons. In Sadore, 24 steers grazed from 09.00 to 19.00 h (day grazers), from 21.00 to 07.00 h (night grazers) or from 09.00 to 19.00 h and from 24.00 to 04.00 h (day and night grazers). In the trials in Toukounous, 64 steers were allotted to 8 treatments (T). Grazing time during the day was for 6 h for T 1, 2 and 3; 9 h for T 4, 5 and 6; 12 h for T7 and 8. Night grazing time was 0 h for T 1, 4 and 7; 3 h for T 2, 5 and 8; and 6 h for T 3 and 6. Feeding activities were observed every 5 min in Sadore. In both studies, forage intake was determined from individual data on faecal output and mean of extrusa in vitro organic matter digestibility. In Sadore, the actual grazing time was 352, 376 and 476 min/day (SEM = 16) for day, night, and day and night grazers, respectively. Night grazers spent less (P<less than>0.05) time ruminating and walking than day grazers. Day and night grazers had a higher forage intake than either day or night grazers. In Toukounous, day and night grazers (T 2, 3, 5, 6 and 8) also consumed more forage than day grazers (T 1, 4 and 7) in all seasons. Forage intake increased with an increase in total duration of grazing, while it declined as the season progressed from wet to dry. These results suggest that timing (day or night) and duration of grazing affect forage intake. Additional grazing time during the night leads to increased forage intake by grazing cattle and consequently provides opportunities for increased animal production in the Sahel.